MICROSCALE CHEMISTRY IN LATIN AMERICA - Ibáñez, Jorge G.; Centro Mexicano de Química en Microescala, Departamento de Ingeniería y Ciencias Químicas, Universidad Iberoamericana, México, D.F (2005)
A brief account of the development of Microscale Chemistry in Latin America is here presented. The US National Microscale Chemistry Center (Merrimack College, Massachusetts) was instrumental in the initiation of several centers. Its Mexican counterpart, the Mexican Microscale Chemistry Center (CMQM), has been a key player in this process. Other participating countries include Argentina, Bolivia, Brazil, Chile, Cuba, Guatemala, Perú and Uruguay.